Domestic Violence and Development Implications in Budaka District - Lubaale, Grace (EUREKA: Social and Humanities, 2022)
Budaka is one of the 146 districts in Uganda experiencing domestic violence (DV) with 5016 cases, recorded in 2020. This was a significant number with obvious development repercussions despite relevant regulations, prohibiting the vice. The purpose of this study is to determine the nature and causes of domestic violence in Budaka district, development implications, and then suggest a course of action. A mixed-methods approach that included desk review and interviews to obtain quantitative and qualitative data, respectively was used. Domestic violence affects people of all ages, education levels, income levels, social standing, and religions, and manifests itself in form of physical, economic, sexual, political, religious, cultural and psychological. Poverty, culture, ethical and moral failure, biological vulnerability of women, and difficulties in obtaining evidence are the causes of domestic violence with far-reaching economic, political, and social development implications in Budaka district. In conclusion, domestic violence exists in Budaka district as a social construct with enormous developmental ramifications. The study recommends deconstruction through adopting Uganda's National Gender Policy of 2007, gender mainstreaming in the district, enacting by-laws, gender monitoring and evaluation, and strengthening Mifuni NGO in the fight against domestic violence